EFEKTIVITAS BERMAIN TEBAK ISI GELAS UNTUK MENINGKATKAN KETAHANAN DUDUK ANAK HIPERAKTIF DI KELAS PERSIAPAN SLB FAN REDHA PADANG (Single Subject Research) - Nola Intan Putri (Universitas Negeri Padang, 2015)
ABSTRACTAbstract: This research was derived from the problems found in the Preparations class of SLB Fan Redha Padang indicating that hyperactive students got problems to seat calmly in the class during the teaching and learning process. The students seemed to have short seated durability and were unable to sit quietly. To deal with this problem, What’s in the Glass game was applied. The purpose of the research was to reveal whether What’s in the Glass game could improve the seated durability of the hyperactive student. This was an experimental research which applied Single Subject Research (SSR) and A-B-A design. The data gotten in this research were analyzed by using visual analysis of graphic.The result of data analysis showed that in the first baseline condition that consisted of 6 meeting, the mean level was 15,67 and the tendency of direction improved (+). In intervention condition that consisted of 8 metings, the mean level was 3,12, the tendency of direction decreased and the change of data also decreased (-). Furthermore, in the second baseline condition that consisted of 5 meetings, the tendency of direction decreased (-). The percentage of the data overlapped was 0%. Based on these results, it was concluded that playing What’s in the Glass game could enhance the seated durability of the hyperactive student. Based on the result, it was suggested to the teacher to create interesting learning strategy to increase hyperactive students’ seated durability.